NEW RECORDS OF TIGER BEETLES FROM NEW ZEALAND WITH TAXONOMIC AND NOMENCLATURAL NOTES ON THE GENUS NEOCICINDELA (Coleoptera, Cicindelidae) - Cassola, Fabio; Moravec, Jiri (Fragmenta entomologica, 2010)
The present paper deals with several new faunistic data and remarks on the taxonomy and nomenclature of the New Zealand endemic genus Neocicindela Rivalier, 1963, based on examination of type specimens of several taxa. N. novaseelandica (W. Horn, 1892) comb. nov. is restored as an independent species closely related to but well separated from N. helmsi (Sharp, 1886). Field photographs, as well as those of type specimens and some of their characters are given.